A 200mV 32b Subthreshold Processor with Adaptive Supply Voltage Control - Luetkemeier, Sven; Jungeblut, Thorsten; Porrmann, Mario; Rückert, Ulrich (Proc. IEEE Int. Solid-State Circuits Conf. Digest of Technical Papers)
In recent years, subthreshold operation has become a research focus for digital systems with limited energy budget (e.g. mobile, battery-powered devices, radio frequency identification (RFID), wireless sensor networks, or biomedical applications). Subthreshold operation allows for such low power consumption by reducing the supply voltage of the circuit below the threshold voltage of the transistors. As dynamic power depends quadratically on supply voltage, and static power depends exponentially on supply voltage, considerable power savings are achieved. At the same time propagation delays increase due to reduced transistor currents. Effectively, energy consumption per cycle can typically be reduced by a factor of 10 using subthreshold operation.

A 245 GHz CB LNA and SHM mixer in SiGe technology - Mao, Yanfei; Schmalz, Klaus; Borngräber, Johannes; Scheytt, Christoph (SiRF 2012 (Silicon Monolithic Integrated Circuits in RF Systems))
The paper presents a four stage 245 GHz LNA in an f t /f max =280/425 GHz SiGe technology and a 4 th sub harmonic 245 GHz transconductance mixer in an f t /f max =250/300 GHz SiGe technology. The LNA takes advantage of common base (CB) topology for each stage and has 12 dB gain at 245 GHz, while exhibiting a 3 dB bandwidth of 26 GHz. It has a supply voltage of 2V and power dissipation of 28 mW. The transconductance mixer has -7 dB conversion gain at 245 GHz with an LO power of 8 dBm at 61 GHz. The mixer draws 9.8 mA at 3V. Simulation results of the receiver comprising the CB LNA and SHM mixer are given.

A 62GHz Reflectometer for Biomedical Sensor Readout in SiGe BiCMOS Technology - Laemmle, Benjamin; Schmalz, Klaus; Scheytt, Christoph; Kissinger, Dietmar; Weigel, Robert (SiRF 2012 (Silicon Monolithic Integrated Circuits in RF Systems))
In this publication an integrated reflectometer in SiGe BiCMOS technology for sensor readout at 62 GHz is presented. The circuit includes an oscillator, a six-port reflectometer, and a dummy sensor for verification purposes. The circuit has a bandwidth of 8GHz at a center frequency of 62 GHz. It operates at 3.75V supply voltage and consumes 282 mW. The measurement principle is demonstrated and the scattering parameters of the dummy sensor are compared to measurement of a breakout circuit with a commercially available vector network analyzer. The circuit has been fabricated in a 190-GHz SiGe:C BiCMOS technology and occupies an area of 0.9 mm 2 .

122 GHz Radartransceiver und Komponenten in 0.13ym SiGe BiCMOS - Scheytt, Christoph; Debski, Wojciech; Sun, Yaoming; Wang, Ruoyu; Winkler, Wolfgang

Local Navigation Strategies for Multi-Robot Exploration - Tanoto, Andry; Rückert, Ulrich (From Simulation to Experimentation with Mini-Robots)
This paper presents two local navigation strategies for multi-robot systems in performing exploration of unknown environments. The strategies are based on the frontier cell for mapping the environment and navigating in it. Additionally, two coordination strategies are used to solve possible conflicts among robots. Key criteria investigated are the efficiency and effectiveness represented by the completion time, traveled distance, the total steps, and the task distribution. The developed algorithms are tested in simulations as well as in experiments with Khepera III mini robots running on the Teleworkbench. To evaluate the robustness of the developed algorithms, tests are performed under different environmental configurations and varying numbers of robots. The results show the advantages of both proposed strategies in different situations such as environment types and starting positions.

Multi-Robot System Validation: From Simulation to Prototyping with Mini Robots in the Teleworkbench - Tanoto, Andry; Werner, Felix; Rückert, Ulrich; Sitte, Joaquin (Advances in Autonomous Mini Robots)
One challenging aspect in the development of multi-robot systems is their validation in a real environment. However, experiments with real robots are considerably tedious as experimenting is repetitive and consists of several steps: setup, execution, data logging, monitoring, and analysis. Moreover, experiments also require many resources especially in the case when involving many robots. This paper describes the role of the Teleworkbench as a platform for conducting experiments involving mini robots. The Teleworkbench offers functionality that can help users in validating their robot software from simulation to prototyping using mini robots. A traffic management system is used as a scenario for demonstrating the support of the Teleworkbench for validating multi-robot systems.

Mixed-Signal PSSS-Empfänger - Scheytt, Christoph
PSSS-Dekodierschaltung, dadurch gekennzeichnet, dass das analoge PSSS-Eingangssignal mit N Spreizsequenzen und N Verknüpfungselementen (z. B. Multiplizierer) verknüpft werden und die Ausgangssignale der N Verknüpfungselemente mit N analogen Integrierern auf integriert werden, dass die Integrierer jeweils zum Beginn der empfangenen Spreizsequenzen gleichzeitig mit dem Signal SYNC zurückgesetzt werden, dass der Integrator über die Dauer einer Code-Sequenz das Eingangssignal auf integriert, dass nach der Integration an den Ausgängen der Integratoren jeweils das dekodierte Datensignal anliegt, dass die Ausgangssignale der Integrierer mit N parallelen einem AD-Wandler digitalisiert werden.

mm-Wave SOC and SIP Design for 122 GHz Radar SSensor in the EU-FP7 Project SUCCESS - Sun, Yaoming; Beer, Stefan; Scheytt, Christoph; Wang, Ruoyu; Zwick, Thomas (RF-MST Cluster Workshop on MEMSWAVE 2012)

40 Gb/s VCSEL driver IC with a new output current and pre-emphasis adjustment method - Sedighi, Behnam; Scheytt, Christoph (Microwave Symposium Digest (MTT), 2012 IEEE MTT-S International)
Design of a 40 Gb/s VCSEL driver IC capable of providing up to 10mA current to common-cathode VCSELs is presented. Using low-power bandwidth enhancement techniques, a prototype IC is successfully developed in 180-GHz SiGe BiCMOS technology. Measured results show 34 GHz of bandwidth, open eye diagram with rise/fall time below 10 ps, and power dissipation of 130 mW.

Low-power BiCMOS track-and-hold circuit with reduced signal feedthrough - Sedighi, Behnam; Borokhovych, Yevgen; Gustat, Hans; Scheytt, Christoph (Microwave Symposium Digest (MTT), 2012 IEEE MTT-S International)
this paper presents a new circuit for high-speed BiCMOS track-and-holds. The proposed approach improves the signal feedthrough in the hold mode and the bandwidth in the tracking mode. A prototype circuit is implemented in a 0.13 µm BiCMOS technology, operating at 10 GS/s and consuming 19 mW from 3.3 V supply. It is shown that the circuit is capable of providing a harmonic distortion below −50 dB.

Low-power 20-Gb/s SiGe BiCMOS driver with 2.5 V output swing - Sedighi, Behnam; Ostrovskyy, Philip; Scheytt, Christoph; Stille, Karl Stephan Christian; Böcker, Joachim (Microwave Symposium Digest (MTT), 2012 IEEE MTT-S International)
this paper investigates low-power design of high-speed and high-swing electronic driver circuits. A method to estimate and optimize the power consumption of such driver ICs is presented. A 20-Gb/s driver circuit is fabricated in 0.25 µm SiGe BiCMOS process and an output swing of 2.5 V pp is measured. The driver consumes 0.75 W from 5 V supply.

122 GHz FMCW Radar Transceiver and Components in 0.13µm SiGe BiCMOS Technology - Scheytt, Christoph; Sun, Yaoming (System, MMIC and Package Design for Low-Cost Radar Sensor)

Spurs and Phase Noise for an integrated 8-12 GHZ Fractional-N PLL Synthesizer in SiGe BiCMOS - Koelnberger, Andreas; Herzel, Frank; Heyer, Heinz-Volker; Lia, Enrico; Piironen, Petri; Telle, Holger; Scheytt, Christoph (Simulations and Measurements of In-Band)

Chip-Antenne, Elektronisches Bauelement und Herstellungsverfahren - Wang, Ruoyu; Sun, Yaoming; Kaynak, Mehmet; Scheytt, J. Christoph
Chipantenne (102), umfassend mindestens einen Strahler (114,116), der sich parallel zu einer Hauptoberfläche eines die Chipantenne tragenden Halbleitersubstrats (104) erstreckt, wobei der Strahler auf einer inselartigen Trägerzone (122,124) des Halbleitersubstrats angeordnet ist, die von mindestens einem vollständig mit einem Gas gefüllten Graben (126,128) umgeben ist, welcher das Halbleitersubstrat in dessen gesamter Tiefenerstreckung durchdringt und durch mindestens einen Haltesteg (130,132,134,136) überbrückt ist, welcher eine tragende Verbindung zwischen der Trägerzone und dem übrigen Halbleitersubstrat bildet.

Proceedings of the 1st Workshop on Metamodelling and Code Generation for Embedded Systems - MeCoEs

Proceedings of the 1st International QEMU Users' Forum

An integrated 0.6–4.6 GHz, 5–7 GHz, 10–14 GHz, and 20–28 GHz frequency synthesizer for software-defined radio applications - Osmany, Sabbir A.; Herzel, Frank; Scheytt, J. Christoph (IEEE Journal of Solid-State Circuits)

Analytical Phase-Noise Modeling and Charge Pump Optimization for Fractional-$N$ PLLs - Herzel, Frank; Osmany, Sabbir A.; Scheytt, J. Christoph (IEEE Transactions on Circuits and Systems I: Regular Papers)

Proceedings of the 1st Workshop on Model Based Engineering for Embedded Systems Design

Proceedings of 13th Design Automation and Test in Europe Conference & Exhibition (DATE)

Hardware-dependent Software

Proceedings of the 5th International DAC Workshop of UML for SoC Design

Proceedings of the 4th DAC Workshop on UML for SOC Design

Proceedings of the 1st International Workshop of UML for SoC and Embedded Systems Design

Realizing Multilevel Snapshots in Dynamically Changing Virtualized Storage Environments - Brinkmann, Andre; Effert, Sascha; Heidebuer, Michael; Vodisek, Mario (5th International Conference on Networking (ICN))

Distributed MD - Brinkmann, André; Effert, Sascha; Heidebuer, Michael; Vodisek, Mario (In Proceedings of the International Workshop on Storage Network Architecture and Parallel I/Os)
Data has become the most valuable asset for many companies; loosing important data can cause companies to fail quite immediately. The protection of data inside storage systems is mostly achieved by using a RAID scheme that adds redundant data to user data, enabling recovery from single or multiple disk failures. This protection against data loss in case of a disk failure can be achieved either by dedicated hardware or a software RAID solution. One major advantage of software RAID is that it comes for free as a built-in functionality in many operating systems like Linux or Microsoft Windows. The drawback of the built-in functionality is that it is not suited to run in multiple server environments; synchronization and recovery processes can be corrupted if more than a single server is allowed to access a software RAID volume. In this paper, we present an enhancement for the Linux md-driver that enables a consistent usage of RAID in multiple server environments. Based on the V:DRIVE virtualization environment, RAID volumes can be consistently synchronized and recovered even in distributed environments. Besides the architectural concepts, we present measurements that indicate the viability of this enhanced, distributed version of md.

An integrated Architecture for Business Intelligence support from Application down to Storage - Brinkmann, André; Effert, Sascha; Heidebuer, Michael; Vodisek, Mario; Baars, Henning (In Proceedings of the International Workshop on Storage Network Architecture and Parallel I/Os)
Recent developments both in the business and the technological domain have led to a significant increase in demand for Business Intelligence (BI) infrastructures that can handle huge amounts of data in small time frames. BI applications are increasingly used by large user bases on all management levels; support tasks spanning the complete value chain are based on transactional data and are directly coupled with operational systems in closed loop approaches. To effectively handle the resulting data volume turns out to be an extremely challenging task which encompasses a variety of issues on different levels. We propose an integrated multi layer tool for monitoring, benchmarking, analyzing, and optimizing the performance of such BI infrastructures. Inside this paper we give a coarse outline of the tools architecture and demonstrate the value of distinct measurement points at operating system layer. For that purpose we introduce a kernel based benchmark environment and present first measurement results. The gathered data clearly indicates that a meaningful analysis of performance benchmarks without kernel trace points is of limited value - which shows the necessity to consider a separate component within the tools architecture.

Content Distribution in Heterogenous Video-on-Demand P2P Networks with ARIMA Forecasts - Loeser, Chris; Schomaker, Gunnar; Brinkmann, André; Vodisek, Mario; Heidebuer, Michael (Proceedings of the 4th International Conference on Networking)

Proceedings of the 2nd International DAC Workshop on UML for SoC Design

Proceedings of the 1st International DAC Workshop of UML for SoC Design

Control method for disposing graphical elements - Dangberg, Andreas; Müller, Wolfgang

Storage Management as Means to cope with Exponential Information Growth - Scheideler, Christian; Salzwedel, Kay; Meyer auf der Heide, Friedhelm; Brinkmann, André; Vodisek, Mario; Rückert, Ulrich (Proceedings of SSGRR 2003)
The advances in Internet technology have led to tremendous improvements in business, education, and science and have changed the way we think, live, and communicate. Information exchange has become ubiquitous by the possibilities offered through modern technologies. We are able to offer information 24 hours a day through our web sites and can leave messages every time and from anywhere in the world. This change in communication has led to new challenges. Enterprises have to deal with an information amount that doubles every year. The technological foundation to cope with this information explosion is given by Storage Area Networks (SANs), which are able to connect a great number of storage systems over a fast interconnection network. However, to be able to use the benefits of a SAN, an easy-to-use and efficient management support has to be given to the storage administrator. In this paper, we will suggest new storage management concepts and we will introduce a new management environment that is able to significantly reduce management costs and increases the performance and resource utilization of the given SAN infrastructure.

Performance of distributed algorithms for topology control in wireless networks - Rührup, Stefan; Schindelhauer, Christian; Volbert, Klaus; Grünewald, M. (Proceedings of the International Parallel and Distributed Processing Symposium (IPDPS))
We try to close the gap between theoretical investigations of wireless network topologies and realistic wireless environments. For point-to-point communication, we examine theoretically well-analyzed sparse graphs, i.e. the Yao-graph, the SparsY-graph, and the SymmY-graph. We present distributed algorithms that can be used to build up these graphs in time $O(log n)$ per node without the use of any geo-graphical positioning system. Our algorithms are based only on local knowledge and local decisions and make use of power control to establish communication links with low energy-cost. We compare these algorithms with respect to congestion, dilation, and energy. For congestion we introduce different measures that allow us to investigate the difference between real-world wireless networks and models for wireless communication at a high level of abstraction. For more realistic simulations we extend our simulation environment SAHNE. We use a realistic transmission model for directed communication that uses sector subdivision. Finally, our experimental results show that our topologies and algorithms work well in a distributed environment and we give some recommendations for the topology control based on our simulations.

Directed power-variable infrared communication for the mini robot Khepera - Volbert, Klaus; Grünewald, Matthias; Schindelhauer, Christian; Rückert, Ulrich (Proceedings of the 2nd International Conference on Autonomous Minirobots for Research and Edutainment)
Communication facilities are important in Robotics if several robots have to work together. In this paper, we describe problems and solutions encountered while designing an infrared-based communication device for the mini robot Khepera. In contrast to traditional omnidirectional systems, it features directed, power-variable transmission in eight directions at unit[23.4]kbps up to a range of unit[1m]. It can differentiate incoming data signals from interference from adjacent sectors and can estimate their direction-of-arrival. We model the transmission over the infrared channel and show how interference influences the reception of the data signals. We also describe methods how to reduce these effects. We have tested the performance of the resulted signal processing in a worst case scenario by simulations and in experiments with a prototype implementation. The resulted module is especially suited for experimental evaluation of ad hoc network protocols and for position estimation.

Proceedings of the VHE Workshop

Verfahren zur Steuerung der Anordnung von graphischen Elementen - Dangberg, Andreas; Müller, Wolfgang

Proceedings des Workshops Methoden und Beschreibungssprachen zur Modellierung und Verifikation von Schaltungen und Systemen